A not so incidental ‘incidentaloma’ − pediatric ganglioneuroma-associated cerebellar degeneration and super-refractory status epilepticus: case report and literature review - Aboseif, Albert; Palmer, Kaitlyn; Abrams, Aaron W.; Lachhwani, Deepak; Knight, Elia Margarita Pestana; Valappil, Ahsan Moosa Naduvil; Zeft, Andrew (Frontiers in Neurology, 2023)
Paraneoplastic neurological disorders are rare in children, with paraneoplastic cerebellar degeneration (PCD) considered highly atypical. We describe a 13-year-old girl with progressive neurobehavioral regression, cerebellar ataxia, and intractable epilepsy presenting in super-refractory status epilepticus. After an extensive evaluation, her clinical picture was suggestive of probable autoimmune encephalitis (AE). Further diagnostic testing revealed a molecularly undefined neural-restricted autoantibody in both serum and CSF, raising suspicion over an adrenal mass previously considered incidental. Surgical resection led to a robust clinical improvement, and pathology revealed a benign ganglioneuroma. This report widens the spectrum of paraneoplastic manifestations of ganglioneuroma, reviews the diagnostic approach to antibody-negative pediatric AE, and raises important clinical considerations regarding benign and incidentally found tumors in the setting of a suspected paraneoplastic neurologic syndrome.